STUDI KELAYAKAN USAHA PADA UMKM PAPITO CATERING - Ayu Sulistyorini; Dila Yulia Dwi S; Naila Alfi R; Athia Zainun M; Amanda Zhafiera M; Angelin Sherlina A; Rahma Rina Wijayanti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to determine the business feasibility of the Papito Catering business in terms of production aspects, marketing aspects and financial aspects. The research method used in this research is a qualitative approach with a case study type of research. The data source used to support research is direct interviews with catering business owners. The data analysis used is starting from reviewing data from interviews, then analyzing the data results, continuing to test the validity of the data and finally concluding from the presentation results. The results of the research show that the papito catering business material from the licensing aspect can be said to be quite good, because it has obtained permits from the cooperative department, health department and a halal certificate from the industry and trade department. The technical aspects of papito catering production are located in strategic places that are easily accessible to students. The management aspect can be said to be good, the financial aspect can be said to be adequate and also the economic, social and environmental aspects can be said to be good. Business feasibility analysis for the papito catering business uses technical aspects of production, management aspects, financial aspects, and economic, social and environmental aspects.